2017
DOI: 10.1002/app.45244
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of interlaminar fracture toughness of carbon fiber–epoxy composites using polyamide‐6,6 electrospun nanofibers

Abstract: In this study, carbon fiber-epoxy composites are interleaved with electrospun polyamide-6,6 (PA 66) nanofibers to improve their Mode-I fracture toughness. These nanofibers are directly deposited onto carbon fabrics before composite manufacturing via vacuum infusion. Three-point bending, tensile, compression, interlaminar shear strength, Charpy impact, and double cantilever beam tests are performed on the reference and PA 66 interleaved specimens to evaluate the effects of PA 66 nanofibers on the mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 28 publications
5
85
0
1
Order By: Relevance
“…In fact it is not even known if the sample fails for delamination of for matrix/fiber breakage. Similar experiments, such as 3PB or 4PB [21,24,27,28,32,33,57,59,71,72], ILSS [24,32,53,77], and SBSh [21,33,78] have been performed to investigate behaviour of nanomodified composites under bending loads. Areas of interest are the flexural properties of the laminates and the shear stresses occurring between two laminae.…”
Section: Pure Bendingmentioning
confidence: 99%
“…In fact it is not even known if the sample fails for delamination of for matrix/fiber breakage. Similar experiments, such as 3PB or 4PB [21,24,27,28,32,33,57,59,71,72], ILSS [24,32,53,77], and SBSh [21,33,78] have been performed to investigate behaviour of nanomodified composites under bending loads. Areas of interest are the flexural properties of the laminates and the shear stresses occurring between two laminae.…”
Section: Pure Bendingmentioning
confidence: 99%
“…The nanocomposites thin film can also be manufactured using electrospinning [194][195][196][197] and electrospun [198][199][200] processes. These methods have gained popularity and are found to be an effective technique to also produce the electrospinning/electrospun nano-interlayers [201][202][203][204][205] which toughen the composite laminate. Klein et al [206] reported the ILFT of specimens (satin woven CFRPs) with carbon nanotube/epoxy films.…”
Section: Nanofillers In Interleavementioning
confidence: 99%
“…to also produce the electrospinning/electrospun nano-interlayers [201][202][203][204][205] which toughen the composite laminate. Klein et al [206] reported the ILFT of specimens (satin woven CFRPs) with carbon nanotube/epoxy films.…”
Section: Nanofillers In Interleavementioning
confidence: 99%
“…17,18 In recent years, there is an increasing interest in developing interleaving method to improve interlaminar fracture toughness of composite materials. Various thermoplastic polymers, such as polysulfone (PSF), 19,20 polyetherimide (PEI), 21,22 phenoxy, 5,23 and polyamide (PA) 3,[24][25][26][27][28] are introduced into the interlaminar resin enriched regions of laminated composites in the forms of particles, films or nanofiber veils. The toughness against delamination fractures has increased to different extent through ductile deformation, void formation and crazing, and other mechanisms.…”
Section: Introductionmentioning
confidence: 99%